Mucosal Vaccination: A Promising Alternative Against Flaviviruses - Luria-Pérez, Rosendo; Sánchez-Vargas, Luis A.; Muñoz-López, Paola; Mellado-Sánchez, Gabriela (Frontiers in Cellular and Infection Microbiology, 2022)
The Flaviviridae are a family of positive-sense, single-stranded RNA enveloped viruses, and their members belong to a single genus, Flavivirus. Flaviviruses are found in mosquitoes and ticks; they are etiological agents of: dengue fever, Japanese encephalitis, West Nile virus infection, Zika virus infection, tick-borne encephalitis, and yellow fever, among others. Only a few flavivirus vaccines have been licensed for use in humans: yellow fever, dengue fever, Japanese encephalitis, tick-borne encephalitis, and Kyasanur forest disease. However, improvement is necessary in vaccination strategies and in understanding of the immunological mechanisms involved either in the infection or after vaccination. This is especially important in dengue, due to the immunological complexity of its four serotypes, cross-reactive responses, antibody-dependent enhancement, and immunological interference. In this context, mucosal vaccines represent a promising alternative against flaviviruses. Mucosal vaccination has several advantages, as inducing long-term protective immunity in both mucosal and parenteral tissues. It constitutes a friendly route of antigen administration because it is needle-free and allows for a variety of antigen delivery systems. This has promoted the development of several ways to stimulate immunity through the direct administration of antigens (e.g., inactivated virus, attenuated virus, subunits, and DNA), non-replicating vectors (e.g., nanoparticles, liposomes, bacterial ghosts, and defective-replication viral vectors), and replicating vectors (e.g., Salmonella enterica, Lactococcus lactis, Saccharomyces cerevisiae, and viral vectors). Because of these characteristics, mucosal vaccination has been explored for immunoprophylaxis against pathogens that enter the host through mucosae or parenteral areas. It is suitable against flaviviruses because this type of immunization can stimulate the parenteral responses required after bites from flavivirus-infected insects. This review focuses on the advantages of mucosal vaccine candidates against the most relevant flaviviruses in either humans or animals, providing supporting data on the feasibility of this administration route for future clinical trials.